A 13-Year-Old Boy Who Has Kawasaki Disease Shock Syndrome Presents with Parotitis - Yozgat, Yilmaz; Uzuner, Selcuk; Demir, Aysegul Dogan; Ogur, Mustafa; Yozgat, Can Yilmaz; Turel, Ozden (Journal of Pediatric Intensive Care, 2020)
We report a 13-year-old boy who (initially) had symptoms of toxic shock-like syndrome and mumps. Then, the patient was hospitalized in the pediatric intensive care unit (PICU) because of his ongoing hemodynamic instability (low blood pressure of 70/30 mm Hg and capillary refill time of > 4 seconds). During his stay in the PICU, the patient was treated with fluid resuscitation and vasoactive infusion and at the same time was diagnosed with Kawasaki disease shock syndrome (KDSS), when giant right coronary artery aneurysms were detected on echocardiographic examination. This case illustrates the risk of KDSS in patient who carries both parotitis and toxic shock-like syndrome. The clinicians should be cautious about detecting any types of coronary artery aneurysms in such patients. This is the first case of KDSS associated with parotitis reported in the literature.
Keywords: Kawasaki disease shock syndrome; toxic shock syndrome; parotitis